The Problem of the Relationship Between Language and World in Heidegger and Wittgenstein - de Azeredo, Jéferson Luís (Universidad de Costa Rica, 2020)
This essay aims to demonstrate that there is an approximation between Heidegger and Wittgenstein in relation to language as a description of the world, founding it as reality. The first position is that one should not oppose these two philosophers considering methodology as the only form of definition. The second central position is that Heidegger and Wittgenstein bring philosophical thought to a construction of the world and man because language exists, and language is possible because there is an image of the world.